Robotics demonstration with the Lego EV3 equipment - Silva, J. A. (2017)
Grade 7th students of the school AE Carlos Amarante in Braga have worked this school year with LegoTM EV3 robotics kits provided by the Hands-on Science Network, exploring its different capabilities. In particular they dealt with some challenges using the commands to control the motors based in the data acquired with touch, infrared or sonar sensors.